ANALISIS LOYALITAS PELANGGAN MELALUI KUALITAS PRODUK, HARGA, PELAYANAN DAN KEPUASAN PADA TOKO OUTLET BIRU YOGYAKARTA - Kusumawati, Elly; Adhilla, Fitroh (Jurnal Fokus Manajemen Bisnis, 2019)
This study aims to analyze loyalty analysis customers through product quality, price, service and satisfaction in stores Yogyakarta Blue Outlet. The independent variable used in the study this is roduct quality, price, service and satisfaction. The dependent used is customer loyalty. The population in this study are all consumers who have visited and make purchases at Yogyakarta Blue Outlet stores. Based on the method purposive sampling was obtained by 62 respondents. The type of data usedis primary data. Data obtained by the method of distributing questionnaires which is distributed directly to respondents who meet the criteria needed. Validity and realibility test of the questionnaire which was used as a tool showed that the questionnare is valid and reliable for use. Based on the results of data analysis, there is an influence on product quality to customer satisfaction with a significant value of 0.031 < 0.05 means the first hypothesis is accepted, there is the effect of price on satisfaction consumers with a significant value of 0.016 < 0.05 means that the second hypothesis is accepted, there is an influence of service on customer satisfaction with value significant 0,000 < 0.05 means that the third hypothesis is accepted, there is an influence satisfaction with customer loyalty with a significant value of 0.004 < 0.05 means the fourth hypothesis is accepted. With the Adjusted R square value at stage 1 namely 0.672 and in stage II is 0.118.